PENERAPAN STRATEGI PELAYANAN DENGAN HUBUNGAN MENINGKATKAN KEPUASAN NASABAH PADA PRODUK TABUNGAN ARISAN BAROKAH DI PT. BPR UNISRITAMA PEKANBARU - INDAYU PRASETYA; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Advantages from . BPR Unisritama is to provide service prima are high-quality and reliable, a strategic partner city government boost the real sector in Pekanbaru, and it gives value for the stakeholders optimum. But the phenomenon that faced by this time is promotion programs saving Arisan Barokah which is run by PT. BPR Unisritama was not enough, it can be seen from the number of customers savings account Arisan Barokah is still a little of the number of customers savings account another in rural banks Unisritama Pekanbaru,. and policies in this gift or lot less attractive to customers, in addition, brochure dissemination or lack of leaflets products. Issues of this research is how the application service strategy that will be done. BPR Unisritama in savings product Arisan Barokah and how customer satisfaction in savings product Arisan Barokah. BPR Unisritama Pekanbaru and what is the relationship between the application service strategy to increase customer satisfaction in savings product arisan barokah in. BPR Unisritama Pekanbaru. Research method uses type or research method descriptive quantitative, with technical data collection use the observation, interviews and questionnaires to respondents as many as 92 people. This Research done at PT PBR Unisritama Pekanbaru. research results , based on recapitulation result GobeScan application service strategy savings product Arisan Barokah by. BPR Unisritama Pekanbaru, customer satisfaction for respondents and customer satisfaction in savings product Arisan Barokah in. BPR Unisritama Pekanbaru, has been in accordance with desire and hope for customers. Based on tests, there is the influence of the implementation strategy most dominant service of customer satisfaction saving Arisan Barokah. PBR Unisritama Pekanbaru. For. BPR Unisritama Pekanbaru should always ask customers to convey criticism and she suggested, in order to increase the best service to customers.Key words : Strategy Service, Customer Satisfaction, Unisritama, Pekanbaru